Kepuasan Pelaku Industri Terhadap Upaya Pembangunan Industri di Kabupaten Temanggung - Rosa Calista Prihestiwi; Samsul Ma'rif (Teknik PWK (Perencanaan Wilayah Kota), 2021)
The industrial sector is considered capable of improving the community's economy. Temanggung Regency become superior industrial investment, this can be proven by the increasing number of industries, the contribution of the industrial sector to the economy of Temanggung Regency, and the number of workers in the industrial sector. Various industrial development efforts have been carried out by the Temanggung Regency Government in order to facilitate industrial activities in Temanggung Regency. Efforts that have been made is developing regions, developing industrial resources, developing industrial facilities and infrastructure, and licensing implementation. Therefore, the purpose of this research is to identify the satisfaction of industrial enterpreneur, who utilize industrial development efforts in Temanggung Regency. The data collection method is questionnaire, while the analytical method is the Customer Service Index (CSI) analysis to identify the level of satisfaction of industrial enterpreneur and the gap analysis to identify indicators of industrial development efforts that require improvement. The results of this reseacrh is the satisfaction of industrial enterpreneur on "satisfied" level with a value of 69.74%; but there are still indicators of industrial development that need to be improved, that are the sources of finance, the availability of assistance for industrial activities, and involvement in export assistance and promotion of industrial products.